MODIFIKASI PERILAKU REINFORCEMENT POSITIF DAN NEGATIF DALAM PROSES PEMBELAJARAN DI TK PURNAMA MATARAM - Septa Nuriana Dewi; Sukardi; Ika Rachmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation procedures and components ofpositive and negative reinforcement used by teachers in the learning process at TKPurnama Mataram, this research employed a qualitative approach using a casestudy. The research subjects consisted of the principal, Group B teachers, parentsand students. Data analysis was conducted using the Miles and Huberman model,which includes data reduction, data display, and conclusion drawing, while datavalidity was ensured through source and technique triangulation. The result showedthat the implementation of positive and negative reinforcement was carried out in arules, teachers role modeling, observation of childern’s behavior, and the provisionof reinforcement based on the behaviors displayed. Positive reinforcement providedin the form of characters star cards, rewards, praise, applause, thumbs-up gestures,appreciation for parents and star badges to maintain desirable behaviors.Meanwhile, negative reinforcement was implemented through simple reprimands,additional learning time, environmental cleaning activities to reduce desirablebehaviors. The application of both forms of reinforcement its used alternativehelping teacher manage childern’s behavior during the learning process, particularlyin improving discipline, social-emotional development, and moral religious value.